Ion Liquid Modified GO Filler to Improve the Performance of Polymer Electrolytes for Li Metal Batteries - Hu, Zhongliang; Zhang, Xiaojing; Liu, Jilei; Zhu, Yirong (Frontiers in Chemistry, 2020)
Polymer electrolytes for Li metal batteries (LMBs) should be modified to improve their ionic conductivity and stability against the lithium electrode. In this study, graphene oxide (GO) was modified by ion liquid (IL), and the IL modified GO (GO-IL) had been used as a filler for polyethylene oxide (PEO). The obtained solid polymer electrolyte (SPE) is of high ionic conductivity, low crystallinity and excellent stability against the lithium electrode. The PEO/GO-IL was characterized by various techniques, and its structure and performance were analyzed in detail. By addition of 1% GO-IL, the conductivity of the PEO/GO-IL SPE reaches 1.8×10-5 S cm-1 at 25 oC, which is 10 times higher than PEO (1.7×10-6 S cm-1), and the current density for stable Li plating/stripping in PEO/GO-IL can be increased to100 µA cm-2 at 60 oC. LiFePO4/Li cell (using PEO/GO-IL SPE) tests indicated that the initial discharge capacity can reach ~145 mA h g-1 and capacity retention can maintain 88% even after 100 cycles at a rate of 0.1C and at 60 oC. Our creative work could provide a useful method to develop SPEs with excellent performance, thus accelerating the commercial application of LMBs.